Land Suitability and Purposed Land Use of Selaru Island, West-Southeast Moluccas Regency - Marthen Pasang Sirappa; Edwin Donald Waas; Andriko Noto Susanto (JOURNAL OF TROPICAL SOILS, 2010)
Land Suitability and Purposed Land Use of Selaru Island, West-Southeast Moluccas Regency (MP Sirappa, ED Waas and AN Susanto): Research was conducted in Selaru Island, West Southeast Moluccas Regency which has areal 32,217 ha. The purpose of the research was to study land suitability class and directive of land use for developing food crop and estate plant. The results  indicated  that Selaru Island was suitable land (S) for upland rice, corn, peanuts, mungbean, sweet potato, calladium, and coconut which had areal of 28,312 ha, 19,330 ha, 19,330 ha, 19,330 ha, 19,330 ha, 28,312 ha, and 12,886 ha, respectively.  Land which was not suitable creteria (N) for upland rice, corn, peanuts, mungbean, sweet potato, calladium, coconut, and cacao were 3,905 ha, 12,887 ha, 12,887 ha, 12,887 ha, 12,887 ha, 3,905 ha, 19,331 ha, and 32,217 ha, respectively. Llimiting factors of land use for dryland food crop and estate plant in survey location were high temperature, root media (shallow soil solum), retention of nutrient (rather alkaline - until alkaline), medium erosion level and terrain (wavies, rock at soil surface and rock outcrop). Purposed  land use for food crop dyland and estate plant based on land suitability class were (1) public coconut estate with main commodity coconut in the areal of 1,947 ha, (2) food crop dryland-1 with main commodities corn, mungbean, purplish edible tuber, and calladium with a wide was 5,299 ha, (3) food crop dryland-2 with main commodities upland rice, purplish edible tuber, and calladium in the areal of was 8,982 ha, and (4) food crop dryland-3 with main commodities peanuts and mungbean in the areal of 14,031 ha